2016
DOI: 10.1097/ede.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Mortality Among Breast Cancer Survivors

Abstract: Background Cardiovascular disease (CVD) is of increasing concern among breast cancer survivors. However the burden of this comorbidity in this group relative to the general population, and its temporal pattern, remains unknown. Methods We compared deaths due to CVD in a population-based sample of 1,413 women with incident breast cancer diagnosed in 1996-1997, and 1,411 age-matched women without breast cancer. Date and cause of death through December 31, 2009 were assessed through the National Death Index and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
278
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(295 citation statements)
references
References 42 publications
10
278
0
7
Order By: Relevance
“…Этот повышенный риск проявля-ется примерно через 7 лет после постановки диагноза РМЖ. В течение этого периода целесообразны ранняя диагностика и активное лечение факторов риска ССЗ, поскольку могут снизить вероятность развития самого ССЗ [11].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…Этот повышенный риск проявля-ется примерно через 7 лет после постановки диагноза РМЖ. В течение этого периода целесообразны ранняя диагностика и активное лечение факторов риска ССЗ, поскольку могут снизить вероятность развития самого ССЗ [11].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…Cardiovascular disease risk was often conceptually defined as incidence of cardiovascular diseases including ischemic heart disease, congestive heart failure, myocardial infarction, coronary artery disease, stroke, angina, atrial fibrillation, paroxysmal tachycardia, nonrheumatic valve disease, cardiomyopathy, aortic aneurysm, and arteriosclerosis. [3][4]8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] While one study included angina as a cardiovascular disease risk factor, 15 Darby et al indicated that angina would not be included as a risk factor due to difficulty with clinical identification of angina. 19 Other investigators conceptually defined cardiovascular disease risk as the presence of cardiovascular disease risk factors including smoking and having an overweight or obese body mass index.…”
Section: Conceptual Definitionsmentioning
confidence: 99%
“…Incidence of cardiovascular diseases using morbidity and mortality was a common measure of cardiovascular disease risk among breast cancer survivors. 4,8,[14][15][16][17][18][19][20][21][22][24][25][26][27]29 Authors of these studies used electronic health records, large databases, and/or linkages to death indexes as data sources. Physical measurements of cardiovascular disease risk are ideal to reduce self-report bias; however, fewer studies conducted physical measurements of cardiovascular disease risk.…”
Section: Operational Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing population of cancer-survived patients have a substantial risk of developing cardiovascular diseases due to ageing, co-morbid CV risk factors and cancer-specific adverse effects related to the malignancy itself or treatment toxicity [2]. Cardiovascular diseases have a significant impact on the quality of life and prognosis of cancer-survived patients and are considered the major non-malignant cause of mortality [3][4][5]. The incidence of CV complications is difficult to estimate precisely due to variability in definitions, the presence of comorbid diseases affecting CV system and data collection stems mainly from registries and case series.…”
Section: Introductionmentioning
confidence: 99%